Comportamento da pimenta biquinho (Capsicum chinense) submetida a diferentes lâminas de irrigação e substratos - Rodrigues, Silvana Antunes (2017)
Peppers are sensitive to water stress, which can lead to damages to their growth and development that directly reflect the final production and thus the use of an ideal cultivation medium for these cultivars will promote water retention and aeration necessary for the crop. In this way, the main objective of this work was to evaluate the response of the biquinho pepper culture in different substrates and irrigation levels. The experiment was conducted in a greenhouse located at the Universidade Federal do Pampa – Campus Alegrete. The plants were seeded in trays of 128 cells and transplanted into pots with a capacity of 2.6 L. The experimental design was completely randomized with a 2x5 factorial treatment, with 2 treatments of substrate composition and 5 treatments of irrigation levels. The substrate composition treatments were commercial substrate and commercial substrate mixture + carbonized rice husk. After the evaluation of pots retention capacity for both substrates, the treatments were determined for the water replacement levels: 25, 50, 75, 100 and 125% of pot retention capacity. During the crop cycle, the components of leaf area index and fresh and dry mass of the aerial and root parts were evaluated, and at the end of the cycle, plant height and stem diameter, and crop yield components, diameter, length, average weight, number of fruits and production, besides the efficiency of water use. The yield components and the water use efficiency are higher when the commercial substrate + carbonized rice husk composition is used. The production has higher results with an irrigation level of 100% of pot retention capacity. On the other hand, the water use efficiency is higher when using the 50% level.